Buttonscarves's Digital Content Marketing On Its Social Media Instagram Account To Maintain Brand - Yopita, Linda; Kurnianingsih, Asih (LPPM Universitas Banten jaya, 2024)
This research aims to understand various strategies in managing digital marketing content on the Instagram account of Buttonscarves to maintain brand image. The research uses a descriptive qualitative method with interview techniques and documentation collection. The subjects of the study are employees at Buttonscarves, specifically from the social media division, and followers of the Buttonscarves Instagram account chosen using purposive sampling. The results of the research indicate that the digital marketing content strategies on the Buttonscarves Instagram account are divided into several stages, namely: 1) Setting Objectives. 2) Target Market Mapping: Focus on followers aged 21-35. 3) Content Ideation and Planning: Includes derivative content (adaptations of existing content) and original content (new and creative material). 4) Content Distribution: Content is distributed through owned media. 5) Content Creation: The Buttonscarves social media team produces content on a weekly basis. 6) Content Evaluation: Content is evaluated by curating content that is relatable and shareable.7) Content Enhancement: To strengthen content, Buttonscarves improves quality through evaluation and innovation. 8) Content Improvement: Innovations in content are made to align with social trends.